Synthesis, Characterization and Anti Mcf-7 Proliferative Acitivity of Flavonol Derivatives of 2'-Hydroxyacetophenon and 3,4,5-Dimethoxy Benzaldehid - Rokim, Muhamad; Zamri, Adel; Teruna, Hilwan Yuda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Flavonols a derivatives of 2'-hydroxyacetophenon and 3,4,5-dimethoxy benzaldehid has been synthesized under basic condition (KOH). The structure of the compound was characterized based on the interpretation of spectroscopic data, including UV, FTIR, NMR and HRMS. Anticancer activity was evaluated using the MTS assay against MCF-7 cells, which showed that the flavonol 2'-hydroxycalone derivative was potentially active as an anticancer substance with IC50 values <1000 µg / mL.